Archaeological Excavations at Gandi Umar Khan 2003: The First Season - Ali, Ihsan; Jan, Zakirullah (Ancient Pakistan, 2021)
This preliminary report is a summary of the archaeological excavations carried out at the proto-historic site of Gandi Umar Khan in southwestern Dera Ismail Khan District in northwest Pakistan. The authors conducted this fieldwork in the year 2003 under the banner of the Directorate of Archaeology and Museums (hereafter Directorate), Government of the Khyber Pakhtunkhwa (formerly called as NWFP) in collaboration with the Department of Archaeology, University of Peshawar in order to investigate the protohistoric cultures in this significant part of South Asia (Ali and Jan 2009). A second (and in fact the last) season of field investigation at the same site was also conducted in the following year i.e. 2004, which, however, would be described separately later on.